PERWUJUDAN SENI PRASI PALELINTANGAN - I Putu Yoga Satyadhi Mahardika; I Wayan Sudiarta; I Gusti Made Budiarta (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
Prasi is an illustration made on palm leafs from antiquity to the present day. This study aims to (1) describe the explanation regarding the stages of treatment of the material, namely palm leafs in the process of making palelintangan prasi, (2) describe the visual elements that make up palelintangan prasi, (3). Describing the form of presentation of the work of palelintangan prasi. The subject in this research is prasi while the object in this research is palelintangan. This research is a qualitative descriptive study. The data collection in this study used the techniques of (1) observation, (2) interviews, (3) discussions, (4) documentation, (5) literature. The results of this study show (1) The form of treatment of rontal leafs as raw materials for making prasi art works is carried out starting from the design design stage, preparing tools and materials such as rontal leafs that are ready to use, teak plywood, rontal leafs attached to the plywood using glue until at the stage of cutting the rontal leafs, sanding, and until the rontal leafs are ready to be incised, (2). Potential visual elements are manifested as meaningful iconography into prasi, (3) Palelintangan prasi is presented using mica glass instead of cute like the presentation of two-dimensional works in general such as drawings or paintings so that they are easily appreciated by art connoisseurs. Keywords: Prasi, Palelintangan, Ront